The Adaptation of Psychological Scales - K. Zülfikar DENİZ (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The exchange of knowledge and information is rapidly progressing and the intercultural interaction is gradually developing in these days. The psychological scales developed for a culture can also be used in different ones. Therefore, it must be answered that how appropriate in another culture the scale is?, how strong the psychometrics of scale (reliability and validity are)? and how accurately the scale reflects the psychological properties of new culture?. Adaptation is to translate the scale into another language and to search answers to these questions above. The aim of this study is to depict the adaptation process of psychological measurement scales, the projects of TIMMS, TIMMSR, OECD/PISA, the reason of adaptation instead of developing a measurement scale, International Test Commision (ITC), ITC activities and test adaptation guide